Nordic Scots pine vs. selected competing species and non-wood substitute materials in mechanical wood products. Literature survey - Grekin, Mika (Finnish Forest Research Institute, 2006)
In this study, Nordic Scots pine wood is benchmarked, based on literature, against selected competing tree species and non-wood substitute materials in selected end-use segments of mechanical wood products. In joinery, interior, and furniture products, the comparisons were made against Western red cedar, ponderosa pine, loblolly pine, and radiata pine, whereas in segment of structural products, lodgepole pine, Norway spruce, and Douglas-fir were included into the study. It should be noted that the material comparisons are valid for small clear wood specimens, not exactly for sawn timber. With respect to the substitute materials, the comparisons were made against a variety of materials in joinery products (case window frames), exterior cladding (siding), and structural products.Based on the literature findings, the main strengths, the weaknesses that could be improved, and the weknesses that must be accepted were concluded for Nordic Scots pine wood as a raw material for joinery products, exterior claddings, and structural products and their end-uses. Compared to the competing tree species, Nordic Scots pine wood is quite superior in the strength and the stiffness properties essential for joinery, interior, and furniture products, as well as for structural products. The variation in several wood properties is the higher the southerly is the geographical origin; with this respect, Scots pine wood from the Nordic countries is more homogeneous compared to wood from the more southerly latitudes. In general, Nordic Scots pine wood is a suitable material for a wide selection of joinery, interior, and furniture products when it is processed and treated properly, and moderately high-quality wood material is selected. Also in structural uses Nordic Scots pine wood is well able to compete against other species, even if moderately large variations may be expected, especially in the strength and stiffness properties due to the geographical origin, knottiness properties, grain angle, and other background variables. Compared to the competing non-wood substitute materials, the main problems of wood as a raw material for several end-uses are associated with the large variations in a variety of properties, as well as with the hygroscopicity and anisotropy of wood material. The main strengths of wood are based on good overall mechanical performance, operational safety and friendliness to the environment, and on the fact that wood is a well-known, traditional material.
Keywords: mekaaninen puunjalostus; puun ominaisuudet; aesthetic properties; exterior claddings; furniture; joinery products; mechanical properties; morphological properties; physical properties; processing properties; structural products